Leadership, Power Distance, and Employee Engagement in a Family-Owned Business - Nešetřil, Daniel (2025)
This thesis explores the relationship between leadership styles, power distance, and employee engagement in family-owned businesses. The research focuses on two Czech SMEs, Grano Skuteč and Forplast Skuteč, both operating in traditional, craft-based industries. The theoretical framework is grounded in existing literature on transformational, authoritarian, democratic, and laissez-faire leadership styles, as well as Hofstede’s concept of power distance. A mixed-method approach was used, combining semi-structured interviews with members of the founding families and quantitative questionnaires distributed to employees. The study examines how leadership styles influence communication, motivation, and inclusion, particularly in contexts where family ties and organizational hierarchy intersect. Findings suggest that transformational and democratic leadership tend to foster higher engagement and lower perceived power distance, while authoritarian approaches may hinder open communication and motivation. The cultural and economic background of the Czech Republic also plays a role in shaping leadership behavior and employee expectations. Limitations include the small sample size, personal ties between the researcher and participants, and the industry-specific nature of the businesses studied. Nevertheless, the thesis provides practical insights for improving leadership and engagement strategies in family enterprises. The research offers recommendations to help leaders balance tradition and innovation while creating inclusive environments for both family and non-family employees.